Injectable heterogeneous cascade nano-enzyme antibacterial hydrogel as well as preparation method and application thereof

By depositing ceria nanoenzymes and glucose oxidase on the surface of molybdenum disulfide nanoparticles, heterogeneous cascade nanoenzyme materials are formed, and the problems of nanophotothermal materials stability and promoter safety in the prior art are solved, and an efficient antibacterial hydrogel is achieved, which improves its biocompatibility and medical application potential.

CN119818718APending Publication Date: 2025-04-15JIANGXI SCI & TECH NORMAL UNIV

Patent Information

Application Number
CN202510166241.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

While improving the antibacterial effect, existing injectable hydrogels have problems with the stability of nanophotothermal materials and the safety and biocompatibility limitations of the use of promoters such as borax, which affects their application in the field of biomedical.

Method used

By depositing ceria nanoenzymes in situ on the surface of molybdenum disulfide nanoparticles and combining glucose oxidase, heterogeneous cascade nanoenzyme materials are formed, and they are loaded into the hydrogel using inverse micellar method and electrostatic interaction to form an injectable heterogeneous cascade nanoenzyme antibacterial hydrogel with a three-dimensional network structure.

Benefits of technology

It has achieved the improvement of the antibacterial effect and biocompatibility of the hydrogel without the use of toxic accelerators, and enhanced its application potential in the field of biomedical science.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119818718A_ABST
    Figure CN119818718A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and discloses injectable heterogeneous cascade nano-enzyme antibacterial hydrogel as well as a preparation method and application thereof. The preparation method comprises the following steps: in a process of preparing cerium dioxide nano-enzyme by a reverse micelle method, introducing molybdenum disulfide nano-particles with a nano flower-shaped structure so as to deposit the cerium dioxide nano-enzyme on the surfaces of the molybdenum disulfide nano-particles in situ to obtain nano-composite particles; through electrostatic interaction, glucose oxidase is loaded on the surfaces of the nano composite particles to form a heterogeneous cascade nano enzyme material; the preparation method comprises the following steps: uniformly mixing sodium alginate and hyaluronic acid in water, and sequentially adding an NO donor, a heterogeneous cascade nano-enzyme material and a cross-linking agent to obtain the injectable heterogeneous cascade nano-enzyme antibacterial hydrogel. The preparation method is simple, and the injectable heterogeneous cascade nano-enzyme antibacterial hydrogel has a strong antibacterial effect and can be used for preparing the antibacterial hydrogel. Particularly, the compound has a remarkable killing effect on gram-negative bacteria and gram-positive bacteria.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomedical nanomaterials, and in particular to an injectable heterogeneous cascade nanoenzyme antibacterial hydrogel and a preparation method and application thereof. Background Art

[0002] Hydrogel dressings are becoming increasingly popular in clinical practice due to their three-dimensional network structure, which enables them to have good exudate absorption, water retention and gas exchange capabilities.

[0003] Common antibacterial hydrogels include smearable hydrogels, dressing hydrogels and injectable hydrogels. Among them, injectable hydrogels have become a research hotspot in the medical field because they can be easily adjusted to the desired shape to meet the needs without surgical operations.

[0004] In the prior art, most of the current injectable hydrogels are made by loading antibiotics, etc. with hydrogels with high specific surface area and high porosity as carriers. Although antibiotics can promote wound healing to a certain extent, due to severe bacterial infection, wounds are often colonized by multiple bacteria, and bacterial cross-infection can lead to bacterial colony effects, thereby producing strong resistance to antibiotics.

[0005] In order to solve the above technical problems, those skilled in the art propose that antibiotic drugs can be replaced by introducing nano-photothermal materials to simulate nano-biological enzymes, but the prior art is that when nano-photothermal materials are loaded in hydrogel materials, due to the poor stability of nano-photothermal materials, other materials such as borax are often added to promote the cross-linking of nano-photothermal materials and hydrogels to improve their stability, such as the preparation method of an injectable antibacterial hydrogel for promoting healing of diabetic infection wounds provided by the prior art CN117085170A, by adding borax to make it cross-linked with copper-tannic acid nanosheets to improve the stability of copper-tannic acid nanosheets. However, since borax has certain toxicity, after being injected into the human body, there will be various aspects such as safety, biocompatibility and clinical application that are restricted, thereby greatly affecting the application of hydrogels in the biomedical field. Summary of the invention

[0006] In order to solve the above-mentioned deficiencies in the prior art, the present invention provides an injectable heterogeneous cascade nanozyme antibacterial hydrogel and a preparation method and application thereof.

[0007] The injectable heterogeneous cascade nanozyme antibacterial hydrogel and its preparation method and application of the present invention are achieved through the following technical solutions:

[0008] The first object of the present invention is to provide a method for preparing an injectable heterogeneous cascade nanozyme antibacterial hydrogel, comprising the following steps:

[0009] Step 1, in situ deposition of cerium dioxide nanozymes on the surface of molybdenum disulfide nanoparticles:

[0010] 1) Ultrasonic dispersion of cerium salt in oleylamine, followed by addition of xylene and mixing, followed by heating to 85° C. to 95° C., and addition of water to obtain a cerium dioxide nanozyme seed solution.

[0011] 2) Using molybdenum disulfide nanoparticles with a nanoflower-like structure as spatially confined carriers, dropping them into the cerium dioxide nanozyme seed solution to obtain a mixed solution; heating the mixed solution at 85° C. to 95° C. to allow the mixed solution to undergo a reverse micelle reaction, in situ depositing the cerium dioxide nanozyme on the surface of the molybdenum disulfide nanoparticles, centrifuging, washing, and then freeze-drying to obtain nanocomposite particles.

[0012] Step 2, loading glucose oxidase:

[0013] In a solution environment, the nanocomposite particles are used as carriers and glucose oxidase is used as a load. The glucose oxidase is loaded on the surface of the nanocomposite particles through electrostatic interaction to obtain a heterogeneous cascade nanoenzyme material.

[0014] Step 3, cross-linking to form a hydrogel:

[0015] 1) Evenly disperse sodium alginate and hyaluronic acid in water to obtain a hydrogel base solution.

[0016] 2) Dispersing the NO donor and the heterogeneous cascade nanozyme material in the hydrogel base liquid in sequence to obtain a hydrogel precursor liquid.

[0017] 3) adding a crosslinking agent to the hydrogel precursor solution so that the hydrogel base solution is fully crosslinked under the action of the crosslinking agent to form a hydrogel with a three-dimensional network structure. At the same time, the NO donor and the heterogeneous cascade nanozyme material are uniformly dispersed in the three-dimensional network structure of the hydrogel to obtain the injectable heterogeneous cascade nanozyme antibacterial hydrogel.

[0018] In step 1, it should be noted that the present invention takes into account that molybdenum disulfide nanoparticles are a nanophotothermal material with near-infrared light radiation characteristics, and have excellent properties such as multiple enzyme activities, low toxicity, good biodegradability and high photothermal conversion capacity. However, in recent years, only its function in simulating biological enzyme activity has been developed, and its ability to load multiple biological enzymes at the same time has not been fully utilized. The surface of ultra-small ceria nanozymes has abundant oxygen vacancies, Ce 3+ and Ce 4+It can be reversibly transferred, so as to have excellent catalase catalytic activity. Therefore, the present invention adopts the strategy of spatial confinement and cascade effect, with molybdenum disulfide nanoparticles as carriers and cerium dioxide nanozymes as loads, so that the cascade nanozyme effect is improved by responding to near-infrared irradiation, giving full play to its excellent peroxidase enzyme activity, and being able to quickly catalyze the generation of active oxygen-hydroxyl radicals in the presence of peroxides, and continuously accumulating hydroxyl radicals under the condition that glucose oxidase GOx continuously provides H2O2, and enhancing the bactericidal effect through the cascade effect.

[0019] The present invention adopts a reverse micelle method to prepare cerium dioxide nanozymes to ensure that the obtained cerium dioxide nanozymes have the characteristics of ultra-small size of 3nm to 5nm and uniform size, and in the process of preparing cerium dioxide nanozymes by the reverse micelle method, molybdenum disulfide nanoparticles with a nanoflower structure are introduced as spatially confined carriers, so that the cerium dioxide nanozymes prepared by the reverse micelle method can be evenly distributed and loaded on the surface of the molybdenum disulfide nanoparticles to form a heterogeneous structure.

[0020] In a preferred embodiment of the present invention, the cerium salt is cerium chloride heptahydrate to provide a cerium source. In a preferred embodiment of the present invention, the ratio of oleylamine to the cerium salt is 3 mL to 4 mL: 0.1 mmol, and the ratio of xylene to the cerium salt is 10 mL to 20 mL: 0.1 mmol, to ensure that the added cerium salt, oleylamine and xylene can form ultra-small cerium dioxide nanozymes through reverse micelle reaction.

[0021] In a preferred embodiment of the present invention, in the ceria nanozyme seed solution, 0.8 mL to 1.2 mL of water is added for every 0.1 mmol of cerium salt.

[0022] In a preferred embodiment of the present invention, the dosage ratio of the molybdenum disulfide nanoparticles to the cerium salt is 0.5 to 1:1, so that the loading amount of the formed cerium dioxide nanozyme is more than 50% of the total mass of the molybdenum disulfide nanoparticles, so as to further promote the uniformity of the distribution of the cerium dioxide nanozyme on the surface of the molybdenum disulfide nanoparticles.

[0023] In order to improve the morphology of molybdenum disulfide nanoparticles and improve the loading efficiency of cascade nanozymes, the present invention preferably uses molybdenum disulfide nanoparticles with a nanoflower-like structure as a spatially confined carrier. For example, to ensure that the molybdenum disulfide nanoparticles used in the present invention have a nanoflower-like structure, in a preferred embodiment of the present invention, the molybdenum disulfide nanoparticles used are prepared by the following steps:

[0024] 1) Mixing polyethylene glycol PEG-400 and water to obtain a mixed solvent. In particular, the present invention takes into account the factors of obtaining molybdenum disulfide nanoflowers with excellent morphology. In some more preferred embodiments of the present invention, PEG-400 and water are mixed in an equal volume ratio to achieve the purpose of preparing molybdenum disulfide nanoflowers with good dispersibility and excellent morphology.

[0025] 2) Dispersing ammonium molybdate tetrahydrate and thiourea in the mixed solvent obtained above, and then performing a hydrothermal reaction, so that ammonium molybdate tetrahydrate and thiourea react at high temperature during the hydrothermal reaction to obtain molybdenum disulfide nanosheets with a sheet structure, thereby obtaining nano molybdenum disulfide. Wherein, in some more preferred embodiments of the present invention, the temperature of the hydrothermal reaction is 210°C to 230°C, so that the purpose of molybdenum disulfide nanoparticles with a sheet structure is achieved at this reaction temperature. In order to ensure that the molybdenum disulfide nanosheets are aggregated to form flower-shaped molybdenum disulfide at this reaction temperature, in some other preferred embodiments of the present invention, the time of the hydrothermal reaction is 12h to 24h. In some preferred embodiments of the present invention, in order to ensure that ammonium molybdate tetrahydrate and thiourea can fully react to form molybdenum disulfide nanosheets, the mass ratio of ammonium molybdate tetrahydrate and thiourea is 1.236:2.28. In some preferred embodiments of the present invention, in order to ensure that the mixed solvent used can fully disperse ammonium molybdate tetrahydrate and thiourea, in some preferred embodiments of the present invention, the usage ratio of the mixed solvent to the ammonium molybdate tetrahydrate is 30mL~40mL:1.236g.

[0026] In order to obtain pure molybdenum disulfide nanoparticles, so as to facilitate the subsequent compounding with the cerium dioxide nanozyme, in some preferred embodiments of the present invention, the reaction solution obtained by the hydrothermal reaction is also subjected to solid-liquid separation to obtain a precipitate. Among them, the solid-liquid separation can be selected from the centrifugal method, and the centrifugal rate is 8000r / min~10000r / min, and the centrifugal time is 5min~10min. Subsequently, ethanol is used as a detergent to wash the obtained precipitate at least twice, and then a mixture of equal volumes of ethanol and water is used as a detergent, and the washing is continued at least once to remove impurities and obtain clean molybdenum disulfide nanoparticles. In order to avoid the possibility that the residual solvent on the surface of the molybdenum disulfide nanoparticles may be applied to subsequent treatment, in some preferred embodiments of the present invention, it is also dried to remove excess solvent. The present invention takes into account the factors of the solvent in the weighing process, so the present invention preferably freeze-drying is used for drying, and the freeze-drying temperature is -50℃~-55℃, and the time is 4h~12h.

[0027] In some preferred embodiments of the present invention, the molybdenum disulfide nanoparticles with a nanoflower-like structure are first dispersed in water to form a molybdenum disulfide nanoparticle dispersion, and then the molybdenum disulfide nanoparticles are dispersed and dropped into the cerium dioxide nanozyme seed solution and mixed to promote the dispersion uniformity of the molybdenum disulfide nanoparticles and the cerium dioxide nanozyme seed solution.

[0028] Among them, in some preferred embodiments of the present invention, ultrasonic dispersion is used to disperse the molybdenum disulfide nanoparticles, and the ultrasonic dispersion time is 5 minutes to 15 minutes to ensure that the molybdenum disulfide nanoparticles can be evenly dispersed in water.

[0029] In some preferred embodiments of the present invention, the ultrasonic power is 300W and the ultrasonic frequency is 40kHZ.

[0030] In some more preferred embodiments of the present invention, in the molybdenum disulfide nanoparticle dispersion, 1 mL of water is added for every 150 μg to 250 μg of molybdenum disulfide nanoparticles to ensure that the amount of water added can fully disperse the molybdenum disulfide nanoparticles.

[0031] In some preferred embodiments of the present invention, the heating reaction time is 2 h to 6 h to ensure that the cerium dioxide nanozyme is uniformly loaded and confined on the surface of the molybdenum disulfide nanoparticles.

[0032] In some preferred embodiments of the present invention, the reaction liquid of the heating reaction is separated into solid and liquid by centrifugation, and the centrifugal speed is 8000r / min to 10000r / min, and the centrifugal time is 5min to 10min.

[0033] In some preferred embodiments of the present invention, when washing the product after solid-liquid separation, ethanol is used as a detergent to wash the obtained precipitate at least twice, and then a mixture of equal volumes of ethanol and water is used as a detergent to continue washing at least once to remove impurities and obtain clean molybdenum disulfide nanoparticles.

[0034] In some preferred embodiments of the present invention, the washed product is further freeze-dried to remove the residual solvent on the surface of the washed product, and the freeze-drying temperature is -50°C to -55°C, and the time is 4h to 12h.

[0035] In step 2, it should be noted that, in order to enable the glucose oxidase to be evenly loaded on the nanocomposite particles, the present invention preferably mixes the nanocomposite particles and glucose oxidase in a solution environment so that the glucose oxidase can fully contact the nanocomposite particles, thereby enabling the glucose oxidase to be evenly loaded on the surface of the nanocomposite particles, thereby obtaining a heterogeneous cascade nanoenzyme material with uniform component distribution.

[0036] In some preferred embodiments of the present invention, the mass ratio of the glucose oxidase to the nanocomposite particles is 1.8-2.2:1 to ensure the composite effect of the glucose oxidase and the nanocomposite particles.

[0037] In some preferred embodiments of the present invention, the heterogeneous cascade nanozyme material is prepared by the following steps:

[0038] The nanocomposite particles are dispersed in water to obtain a nanocomposite particle dispersion; glucose oxidase is dispersed in water to obtain a glucose oxidase aqueous solution; the glucose oxidase aqueous solution is dropped into the nanocomposite particle dispersion, and the reaction is stirred at room temperature to load the glucose oxidase on the surface of the nanocomposite particles through electrostatic interaction, and the solid-liquid separation is performed. After freeze-drying the precipitate, a heterogeneous cascade nanoenzyme material is obtained.

[0039] In some preferred embodiments of the present invention, the stirring reaction time is 8 hours to 16 hours to ensure that the glucose oxidase can be evenly loaded on the surface of the nanocomposite particles through the stirring reaction.

[0040] In some preferred embodiments of the present invention, the nanocomposite particles are dispersed by ultrasound, and the ultrasound time is 5 minutes to 15 minutes to ensure that the nanocomposite particles can be evenly dispersed in water. In some preferred embodiments of the present invention, the ultrasound power is 300W and the ultrasound frequency is 40kHZ.

[0041] In some preferred embodiments of the present invention, in the nanocomposite particle dispersion, 0.8 L to 1.2 L of water is added per 1 g of nanocomposite particles to ensure that the amount of water is sufficient to disperse the nanocomposite particles.

[0042] In order to ensure that the amount of water used can fully disperse the glucose oxidase, in some preferred embodiments of the present invention, the concentration of glucose oxidase in the glucose oxidase aqueous solution is 2 mg / mL.

[0043] The present invention takes into account that since the stirring reaction is carried out in a solution environment, the heterogeneous cascade nanozyme material is also present in the solution environment. In order to facilitate the acquisition of pure heterogeneous cascade nanozyme materials, so as to facilitate the subsequent formation of hydrogel materials, in some preferred embodiments of the present invention, the reaction solution obtained by the stirring reaction is also subjected to solid-liquid separation to obtain a precipitate. Among them, the solid-liquid separation can be selected from the centrifugal method, and the centrifugal rate is 8000r / min~10000r / min, and the centrifugal time is 5min~10min. Subsequently, ethanol is used as a detergent to wash the obtained precipitate at least 2 times, and then a mixture of equal volumes of ethanol and water is used as a detergent, and the washing is continued at least once to remove impurities and obtain clean molybdenum disulfide nanoparticles. In order to avoid the possibility that the residual solvent on the surface of the molybdenum disulfide nanoparticles may be applied to subsequent treatment, in some preferred embodiments of the present invention, it is also dried to remove excess solvent. The present invention takes into account the factors of the solvent in the weighing process, so the present invention preferably freeze-drying is used for drying, and the freeze-drying temperature is -50℃~-55℃, and the time is 4h~12h.

[0044] In step 3, it should be noted that the present invention takes into account the factors of solid solvent in the mixing process. In some preferred embodiments of the present invention, sodium alginate and hyaluronic acid are first uniformly dispersed in water to achieve the purpose of uniform mixing of the two. Then the NO donor and the heterogeneous cascade nanozyme material are added and mixed to achieve the simultaneous loading of the NO donor and the heterogeneous cascade nanozyme material, and then the cross-linking agent is added to make the hydrogel base liquid fully cross-linked under the action of the cross-linking agent to form a hydrogel with a three-dimensional network structure. At the same time, the NO donor and the heterogeneous cascade nanozyme material are uniformly dispersed in the three-dimensional network structure of the hydrogel to obtain the injectable heterogeneous cascade nanozyme antibacterial hydrogel.

[0045] In some preferred embodiments of the present invention, the mass ratio of sodium alginate to hyaluronic acid is 1.8-2.2:1, so as to ensure that the added sodium alginate and hyaluronic acid can be fully cross-linked to form a hydrogel with a three-dimensional network structure under the action of a subsequent cross-linking agent.

[0046] In some preferred embodiments of the present invention, in order to make the sodium alginate and the hyaluronic acid fully mixed in water, the sodium alginate and the hyaluronic acid are first dispersed in water to form corresponding sodium alginate solution and hyaluronic acid solution, and then the sodium alginate solution and the hyaluronic acid solution are mixed to obtain a hydrogel base liquid. Wherein, the mass fraction of sodium alginate in the sodium alginate solution is 1.8% to 2.2%, and the mass fraction of hyaluronic acid in the hyaluronic acid solution is 0.8% to 1.2%. When mixing the sodium alginate solution and the hyaluronic acid solution, the volume used only needs to ensure that the mass ratio of sodium alginate to hyaluronic acid is 1.8 to 2.2:1.

[0047] In some preferred embodiments of the present invention, in the hydrogel precursor solution, the added amount of the NO donor is 1 to 1.5 times the added amount of the sodium alginate, and the added amount of the heterogeneous cascade nanozyme material is 0.1 to 0.2 times the added amount of the sodium alginate, so as to ensure that the added heterogeneous cascade nanozyme material and NO donor can be evenly distributed in the hydrogel formed by sodium alginate and hyaluronic acid, thereby giving the hydrogel the spatial confinement effect of the photothermal properties of molybdenum disulfide, the peroxidase activity and glucose oxidase activity of cerium dioxide, and generating reactive oxygen toxic to bacteria through the cascade reaction of the peroxidase activity of cerium dioxide and the glucose oxidase activity. At the same time, the addition of NO donor promotes the formation of new blood vessels and improves microvascular blood flow. The injectable hydrogel is used as a drug delivery system to reduce the toxic side effects of nanomaterials and enhance the drug action efficiency of nanomaterials.

[0048] In some preferred embodiments of the present invention, the heterogeneous cascade nanozyme material is first dispersed in water to form a heterogeneous cascade nanozyme material dispersion, and then the heterogeneous cascade nanozyme material dispersion is added to the hydrogel base liquid to improve the dispersion uniformity of the heterogeneous cascade nanozyme material in the hydrogel base liquid, thereby facilitating the uniform dispersion of the heterogeneous cascade nanozyme material in the three-dimensional network structure of the hydrogel. Among them, in some more preferred embodiments of the present invention, 1L of water is added to every 200mg to 300mg of the heterogeneous cascade nanozyme material in the heterogeneous cascade nanozyme material dispersion.

[0049] In some preferred embodiments of the present invention, the NO donor is L-arginine, which is a good NO donor. Arginine can release NO in situ in response to ROS and nitric oxide synthase, so arginine is delivered for in situ production of NO. NO is an important mediator of vascular autoregulation and has the functional characteristics of promoting angiogenesis and improving microvascular blood flow. In addition, NO can react with ROS to generate peroxynitrite, which is -6 -10 -9 At M concentration, the bacterial film formed by bacteria can be completely eradicated, showing a certain effect on sterilization.

[0050] In some preferred embodiments of the present invention, L-arginine is first dispersed in water to form an L-arginine dispersion, and then the L-arginine dispersion is added to the hydrogel base liquid to improve the uniformity of the dispersion of L-arginine in the hydrogel base liquid, thereby facilitating the uniform dispersion of L-arginine in the three-dimensional network structure of the hydrogel. Among them, in some more preferred embodiments of the present invention, the mass concentration of the L-arginine dispersion is 1.5% to 2.5%, so as to achieve the purpose of successfully loading L-arginine.

[0051] In some preferred embodiments of the present invention, the crosslinking agent is calcium chloride; and the ratio of the crosslinking agent to the sodium alginate is 0.8 to 1.2: 2. In order to promote the full dispersion of calcium chloride and improve its crosslinking effect, in some more preferred embodiments of the present invention, calcium chloride is first dispersed in water to form a calcium chloride aqueous solution with a mass concentration of 0.08 mol / L to 0.12 mol / L, and then added in the form of a calcium chloride aqueous solution to promote the formation of an injectable and uniform hydrogel.

[0052] The second object of the present invention is to provide an injectable heterogeneous cascade nanozyme antibacterial hydrogel as described above.

[0053] The third object of the present invention is to provide an application of the above-mentioned injectable heterogeneous cascade nanozyme antibacterial hydrogel in the antibacterial field.

[0054] In some preferred embodiments of the present invention, the injectable heterogeneous cascade nanozyme antibacterial hydrogel is used to fight pathogenic bacteria; the anti-pathogenic bacteria are one or more of Staphylococcus aureus, Escherichia coli, Bacillus subtilis, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa.

[0055] Compared with the prior art, the present invention has the following beneficial effects:

[0056] The present invention uses molybdenum disulfide nanoparticles with a nano-flower-like structure as a spatially confined carrier, and introduces it in the process of preparing cerium dioxide nanozymes by a reverse micelle method, so as to deposit ultra-small-sized cerium dioxide nanozymes on the surface of the molybdenum disulfide nanoparticles in situ through a reverse micelle reaction to obtain nanocomposite particles. Then, the nanocomposite particles are used as carriers and glucose oxidase is used as a load, and a layer of glucose oxidase is loaded on the surface of the nanocomposite particles through electrostatic interaction to obtain a heterogeneous cascade nanozyme material. After sodium alginate and hyaluronic acid are mixed in water, an NO donor, a heterogeneous cascade nanozyme material and a cross-linking agent are added in sequence, so that the hydrogel base liquid is fully cross-linked under the action of the cross-linking agent to form a hydrogel with a three-dimensional network structure. At the same time, the NO donor and the heterogeneous cascade nanozyme material are uniformly dispersed in the three-dimensional network structure of the hydrogel to obtain an injectable heterogeneous cascade nanozyme antibacterial hydrogel.

[0057] The present invention prepares polyvinyl alcohol-modified molybdenum disulfide nanoflowers by a one-pot hydrothermal method; then a simple reverse micelle method is used to prepare ultra-small uniform cerium dioxide nanozymes, and the cerium dioxide nanozymes and glucose oxidase are successfully confined on the surface-rich molybdenum disulfide nanoflowers by in-situ deposition and self-assembly; finally, the prepared cascade nanozymes and L-arginine are successfully combined with an injectable sodium alginate hyaluronic acid hydrogel by a cross-linking agent calcium ion, and an injectable hydrogel with good biocompatibility and antibacterial activity is obtained. The preparation method of the present invention is extremely simple and the cost is very low, which is very suitable for further promotion.

[0058] The injectable heterogeneous cascade nanozyme antibacterial hydrogel of the present invention makes full use of the spatial confinement effect of molybdenum disulfide nanoflowers and their inherent excellent photothermal properties, produces reactive oxygen toxic to bacteria through the cascade reaction of cerium dioxide peroxidase activity and glucose oxidase activity, and simultaneously adds NO progenitor L-arginine to promote neovascularization and improve microvascular blood flow; the injectable hydrogel is used as a drug delivery system to reduce the toxic side effects of nanomaterials and enhance the drug action efficiency of nanomaterials.

[0059] The injectable heterogeneous cascade nanozyme antibacterial hydrogel of the present invention is a composite of the spatial confinement effect of the photothermal characteristics of molybdenum disulfide and the POD activity of cerium dioxide. It continuously produces ROS through the cascade catalytic effect, enhancing the catalytic activity of a single nanomaterial; in addition, gas therapy is used to synergize the antibacterial properties of nanozymes and promote the formation of new blood vessels by exogenously introducing NO suppliers. The injectable sodium alginate hyaluronic acid hydrogel reduces the toxic side effects of the material and enhances the drug delivery efficiency of the nanomaterial. Both the psoriasis model and the diabetic wound infection model have proven that the hydrogel system has a strong antibacterial and anti-inflammatory effect on the growth and reproduction of bacteria, especially Gram-negative bacteria and Gram-positive bacteria.

[0060] The injectable heterogeneous cascade nanozyme antibacterial hydrogel prepared by the present invention has excellent low cell hemolysis, biocompatibility and in vivo toxicity, and has greater application potential than conventional antibacterial materials; at the same time, it has great application prospects for skin inflammatory diseases. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a photo of the injectable heterogeneous cascade nanozyme antibacterial hydrogel of Example 1.

[0062] Figure 2 This is a photograph of the sodium alginate hyaluronic acid hydrogel of Comparative Example 1.

[0063] Figure 3 This is a scanning electron microscope image of the injectable heterogeneous cascade nanozyme antibacterial hydrogel of Example 1.

[0064] Figure 4 This is a scanning electron microscope image of the sodium alginate hyaluronic acid hydrogel of Comparative Example 1.

[0065] Figure 5 These are scanning electron microscope images of MoS2 of Comparative Example 3 and MoS2@CeO2-GOx of Comparative Example 4; wherein, Figure A is a scanning electron microscope image of MoS2 of Comparative Example 3, and Figure B is a scanning electron microscope image of MoS2 of Comparative Example 4.

[0066] Figure 6 This is a transmission electron microscope image of the heterogeneous cascade nanozyme material of Example 1.

[0067] Figure 7 This is the Zeta potential analysis diagram of the materials provided for Comparative Examples 2 to 5.

[0068] Figure 8 The X-ray photoelectron spectra of Comparative Examples 3 and 4 are shown.

[0069] Fig. 9 Figure 3 is the inhibitory growth curve of different concentrations of MoS2@CeO2-GOx+L-Arg on Staphylococcus aureus and Escherichia coli. Figure A is the inhibitory growth curve of different concentrations of MoS2@CeO2-GOx+L-Arg on Staphylococcus aureus, and Figure B is the inhibitory growth curve of different concentrations of MoS2@CeO2-GOx+L-Arg on Escherichia coli.

[0070] Fig.10 The following are statistical diagrams of the bactericidal kinetics of MoS2@CeO2-GOx+L-Arg against Staphylococcus aureus and Escherichia coli, respectively. Figure A is the statistical diagram of the bactericidal kinetics of MoS2@CeO2-GOx+L-Arg against Staphylococcus aureus, and Figure B is the statistical diagram of the bactericidal kinetics of MoS2@CeO2-GOx+L-Arg against Escherichia coli.

[0071] Fig.11 The in vitro hemolysis rate statistics of MoS2@CeO2-GOx+L-Arg at different concentrations are shown in Figure 2. Fig.11 The illustrations are actual pictures of the samples in each group after shaking and incubating for 1 hour.

[0072] Fig.12 This is a diagram of the wound changes in diabetic mice against Staphylococcus aureus infection after injection of MoS2@CeO2-GOx+L-Arg.

[0073] Fig.13 Quantification of wound area against Staphylococcus aureus infection in diabetic mice injected with MoS2@CeO2-GOx+L-Arg. DETAILED DESCRIPTION

[0074] The technical solutions in the embodiments of the present invention are described clearly and completely below. It should be noted that the glucose oxidase used in the following embodiments of the present invention is purchased from Sangon Biotech (Shanghai) Co., Ltd. And in the following embodiments of the present invention, the ultrasonic power of the ultrasonic treatment involved is 300W, the ultrasonic frequency is 40kHZ, and the ultrasonic time is 5min to 15min, which mainly achieves the effect of promoting dispersion and dissolution.

[0075] Example 1

[0076] This embodiment provides an injectable heterogeneous cascade nanozyme antibacterial hydrogel, which is obtained by the following preparation steps:

[0077] Step 1, in situ deposition of cerium dioxide nanozymes on the surface of molybdenum disulfide nanoparticles:

[0078] 1.1) Preparation of MoS2 nanoparticles with nanoflower-like structure:

[0079] 17.5 mL ultrapure water and 17.5 mL PEG-400 were mixed to obtain a mixed solvent. Ammonium molybdate tetrahydrate was used as a molybdenum source, polyethylene glycol PEG-400 was used as a morphology regulator, and thiourea was used as a sulfur source. 1.236 g of ammonium molybdate tetrahydrate and 2.28 g of thiourea were dispersed in the above-prepared mixed solvent and then transferred to a 100 mL autoclave, heated to 220°C, and then hydrothermally reacted at 220°C for 18 hours, and then cooled to room temperature. The reaction solution of the hydrothermal reaction was centrifuged at 9000 r / min for 5 minutes to 10 minutes, the supernatant was discarded, the precipitate was washed 3 times with ethanol, and the washed product was freeze-dried at -51.5°C for 8 hours to obtain molybdenum disulfide nanoparticles with a nanoflower structure, recorded as MoS2NPs.

[0080] 1.2) Preparation of Ceria Nanozyme Seed Solution:

[0081] Taking cerium chloride heptahydrate as the cerium salt, 37 mg of cerium chloride heptahydrate was ultrasonically dissolved in 3.6 mL of oleylamine, and then 15 mL of xylene was added and mixed with ultrasound for 15 minutes. When the mixture was placed in an oil bath and heated to 90°C, 1 mL of ultrapure water was added to obtain the cerium dioxide nanozyme seed solution.

[0082] 1.3) Introducing MoS2 nanoparticles with nanoflower-like structures as spatially confined carriers:

[0083] 8 mg of the prepared molybdenum disulfide nanoparticles were dispersed in 1 mL of ultrapure water to obtain a molybdenum disulfide nanoparticle dispersion. The molybdenum disulfide nanoparticle dispersion was slowly added dropwise to the cerium dioxide nanozyme seed solution to obtain a mixed solution. The mixed solution was heated at 90°C for 4 hours, cooled to room temperature, and the reaction solution was centrifuged at 9000 r / min for 5 minutes, and then the supernatant was discarded. The precipitate was washed 3 times with ethanol, and the washed product was freeze-dried at -51.5°C for 8 hours to obtain nanocomposite particles, recorded as MoS2@CeO2 NPs.

[0084] Step 2, loading glucose oxidase:

[0085] 5 mg of the above-prepared nanocomposite particles were added to ultrapure water and ultrasonicated for 10 min to obtain a nanocomposite particle dispersion. 10 mg of glucose oxidase was added to ultrapure water and ultrasonicated for 10 min to obtain a glucose oxidase dispersion. The glucose oxidase dispersion was slowly added dropwise to the nanocomposite particle dispersion, stirred and reacted at room temperature for 12 h, and then the reaction solution was centrifuged at 9000 r / min for 5 min, washed twice with water, the supernatant was discarded, the precipitate was retained, and the precipitate was freeze-dried at -51.5 ° C for 8 h to obtain a heterogeneous cascade nanozyme material, recorded as MoS2@CeO2-GOx NPs.

[0086] Step 3, cross-linking to form a hydrogel:

[0087] 3.1) Preparation of hydrogel base solution:

[0088] 20 mg of sodium alginate was ultrasonically dispersed in ultrapure water to obtain a sodium alginate solution with a mass fraction of 2%. 10 mg of hyaluronic acid was ultrasonically dispersed in ultrapure water to obtain a hyaluronic acid solution with a mass fraction of 1%. The sodium alginate solution and the hyaluronic acid solution were mixed to obtain a hydrogel base solution.

[0089] 3.2) Preparation of L-arginine dispersion and heterogeneous cascade nanozyme material dispersion:

[0090] According to the addition amount of L-arginine being 1.3 times the mass of sodium alginate, the addition amount of heterogeneous cascade nanozyme material being 0.18 times the addition amount of the sodium alginate, and the mass ratio of calcium chloride to the sodium alginate being 1:2, respectively weigh the corresponding masses of L-arginine, heterogeneous cascade nanozyme material and calcium chloride for use.

[0091] The weighed L-arginine was ultrasonically dispersed in ultrapure water to obtain a 2% L-arginine dispersion. The weighed heterogeneous cascade nanozyme material was ultrasonically dispersed in ultrapure water to obtain a 250 μg / mL heterogeneous cascade nanozyme material dispersion.

[0092] 3.3) Preparation of hydrogel precursor solution:

[0093] The L-arginine dispersion and heterogeneous cascade nanozyme material dispersion obtained above are added to the hydrogel base liquid, and ultrasonically mixed to obtain a hydrogel precursor solution.

[0094] 3.4) Preparation of cross-linking agent:

[0095] The weighed calcium chloride is ultrasonically dispersed in ultrapure water to obtain a calcium chloride aqueous solution with a mass concentration of 0.1 mol / L.

[0096] 3.5) Cross-linking to form injectable heterogeneous cascade nanozyme antibacterial hydrogel:

[0097] The above-mentioned calcium chloride aqueous solution was added to the hydrogel precursor solution and mixed evenly, and cross-linked for 5 minutes to form a crude hydrogel. The obtained crude hydrogel was placed in liquid nitrogen for 4 hours, and then freeze-dried for 24 hours to obtain the injectable heterogeneous cascade nanozyme antibacterial hydrogel, which was recorded as MoS2@CeO2-GOx+L-Arg.

[0098] Example 2

[0099] This embodiment provides an injectable heterogeneous cascade nanozyme antibacterial hydrogel, which is obtained by the following preparation steps:

[0100] Step 1, in situ deposition of cerium dioxide nanozymes on the surface of molybdenum disulfide nanoparticles:

[0101] 1.1) Preparation of MoS2 nanoparticles with nanoflower-like structure:

[0102] 15 mL of ultrapure water and 15 mL of PEG-400 were mixed to obtain a mixed solvent. 1.236 g of ammonium molybdate tetrahydrate and 2.28 g of thiourea dispersion solution were then transferred to a 100 mL autoclave in the above mixed solvent, heated to 210°C, and then hydrothermally reacted at 220°C for 12 hours, and then cooled to room temperature. The reaction solution of the hydrothermal reaction was centrifuged at 8000 r / min for 5 to 10 minutes, the supernatant was discarded, the precipitate was washed 3 times with ethanol, and the washed product was freeze-dried at -50°C for 12 hours to obtain molybdenum disulfide nanoparticles with a nanoflower structure, recorded as MoS2NPs.

[0103] 1.2) Preparation of Ceria Nanozyme Seed Solution:

[0104] 37 mg of cerium chloride heptahydrate was ultrasonically dissolved in 3 mL of oleylamine, and then 10 mL of xylene was added and mixed with ultrasound for 15 min. When the mixture was heated to 85°C in an oil bath, 0.8 mL of ultrapure water was added to obtain a cerium dioxide nanozyme seed solution.

[0105] 1.3) Introducing MoS2 nanoparticles with nanoflower-like structures as spatially confined carriers:

[0106] 8 mg of the prepared molybdenum disulfide nanoparticles were dispersed in 1 mL of ultrapure water to obtain a molybdenum disulfide nanoparticle dispersion. The molybdenum disulfide nanoparticle dispersion was slowly added dropwise to the cerium dioxide nanozyme seed solution to obtain a mixed solution. The mixed solution was heated at 85°C for 2 hours, cooled to room temperature, and the reaction solution was centrifuged at 8000 r / min for 5 minutes, and then the supernatant was discarded. The precipitate was washed 3 times with ethanol, and the washed product was freeze-dried at -50°C for 12 hours to obtain nanocomposite particles.

[0107] Step 2, loading glucose oxidase:

[0108] 5 mg 9 mg glucose oxidase was added to ultrapure water and ultrasonicated for 10 min to obtain a glucose oxidase dispersion. The glucose oxidase dispersion was slowly added dropwise to the nanocomposite particle dispersion and stirred for reaction at room temperature for 8 h. The reaction solution was then centrifuged at 8000 r / min for 5 min, washed twice with water, the supernatant was discarded, the precipitate was retained, and the precipitate was freeze-dried at -50 ° C for 12 h to obtain a heterogeneous cascade nanozyme material.

[0109] Step 3, cross-linking to form a hydrogel:

[0110] 18 mg of sodium alginate was ultrasonically dispersed in ultrapure water to obtain a sodium alginate solution with a mass fraction of 1.8%. 10 mg of hyaluronic acid was ultrasonically dispersed in ultrapure water to obtain a hyaluronic acid solution with a mass fraction of 1%. The sodium alginate solution and the hyaluronic acid solution were mixed to obtain a hydrogel base solution.

[0111] According to the addition amount of L-arginine being 1 times the mass of sodium alginate, and the addition amount of heterogeneous cascade nanozyme material being 0.1 times the addition amount of the sodium alginate, the corresponding mass of L-arginine and heterogeneous cascade nanozyme material are weighed respectively. And according to the mass ratio of calcium chloride to the sodium alginate of 0.8:2, the corresponding mass of calcium chloride is weighed and set aside.

[0112] The weighed L-arginine was ultrasonically dispersed in ultrapure water to obtain a 2% L-arginine dispersion. The weighed heterogeneous cascade nanozyme material was ultrasonically dispersed in ultrapure water to obtain a 250 μg / mL heterogeneous cascade nanozyme material dispersion. The L-arginine dispersion and heterogeneous cascade nanozyme material dispersion obtained above were added to the above hydrogel base liquid, ultrasonically mixed, and a hydrogel precursor solution was obtained.

[0113] The weighed calcium chloride was ultrasonically dispersed in ultrapure water to obtain a calcium chloride aqueous solution with a mass concentration of 0.08 mol / L. The obtained calcium chloride aqueous solution was added to the hydrogel precursor solution and mixed evenly, cross-linked for 5 minutes to form a crude hydrogel, and the obtained crude hydrogel was placed in liquid nitrogen for 4 hours, followed by freeze drying for 24 hours to obtain the injectable heterogeneous cascade nanozyme antibacterial hydrogel.

[0114] Example 3

[0115] This embodiment provides an injectable heterogeneous cascade nanozyme antibacterial hydrogel, which is obtained by the following preparation steps:

[0116] Step 1, in situ deposition of cerium dioxide nanozymes on the surface of molybdenum disulfide nanoparticles:

[0117] 1.1) Preparation of MoS2 nanoparticles with nanoflower-like structure:

[0118] 20 mL of ultrapure water and 20 mL of PEG-400 were mixed to obtain a mixed solvent. 1.236 g of ammonium molybdate tetrahydrate and 2.28 g of thiourea dispersion solution were then transferred to a 100 mL autoclave in the prepared mixed solvent, heated to 220°C, and hydrothermally reacted at 230°C for 24 hours, and then cooled to room temperature. The reaction solution of the hydrothermal reaction was centrifuged at 10,000 r / min for 5 to 10 minutes, the supernatant was discarded, the precipitate was washed 3 times with ethanol, and the washed product was freeze-dried at -55°C for 6 hours to obtain molybdenum disulfide nanoparticles with a nanoflower structure, recorded as MoS2NPs.

[0119] 1.2) Preparation of Ceria Nanozyme Seed Solution:

[0120] 37 mg of cerium chloride heptahydrate was ultrasonically dissolved in 4 mL of oleylamine, and then 20 mL of xylene was added and mixed with ultrasound for 15 min. When the mixture was heated to 95°C in an oil bath, 1.2 mL of ultrapure water was added to obtain a cerium dioxide nanozyme seed solution.

[0121] 1.3) Introducing MoS2 nanoparticles with nanoflower-like structures as spatially confined carriers:

[0122] 8 mg of the prepared molybdenum disulfide nanoparticles were dispersed in 1 mL of ultrapure water to obtain a molybdenum disulfide nanoparticle dispersion. The molybdenum disulfide nanoparticle dispersion was slowly added dropwise to the cerium dioxide nanozyme seed solution to obtain a mixed solution. The mixed solution was heated at 95°C for 6 hours, cooled to room temperature, and the reaction solution was centrifuged at 10,000 r / min for 5 minutes, and then the supernatant was discarded. The precipitate was washed 3 times with ethanol, and the washed product was freeze-dried at -55°C for 12 hours to obtain nanocomposite particles.

[0123] Step 2, loading glucose oxidase:

[0124] 5 mg of the above nanocomposite particles were added to ultrapure water and ultrasonicated for 10 min to obtain a nanocomposite particle dispersion. 11 mg of glucose oxidase was added to ultrapure water and ultrasonicated for 10 min to obtain a glucose oxidase dispersion. The glucose oxidase dispersion was slowly added dropwise to the nanocomposite particle dispersion, stirred and reacted at room temperature for 16 h, and then the reaction solution was centrifuged at 10000 r / min for 10 min, washed twice with water, the supernatant was discarded, the precipitate was retained, and the precipitate was freeze-dried at -55 ° C for 12 h to obtain a heterogeneous cascade nanozyme material.

[0125] Step 3, cross-linking to form a hydrogel:

[0126] 22 mg of sodium alginate was ultrasonically dispersed in ultrapure water to obtain a sodium alginate solution with a mass fraction of 2.2%. 10 mg of hyaluronic acid was ultrasonically dispersed in ultrapure water to obtain a hyaluronic acid solution with a mass fraction of 1%. The sodium alginate solution and the hyaluronic acid solution were mixed to obtain a hydrogel base solution.

[0127] According to the addition amount of L-arginine being 1.5 times the mass of sodium alginate, the addition amount of heterogeneous cascade nanozyme material being 0.2 times the addition amount of sodium alginate, and the mass ratio of calcium chloride to sodium alginate being 1.2:2, the corresponding masses of L-arginine, heterogeneous cascade nanozyme material and calcium chloride are weighed respectively and set aside.

[0128] The weighed L-arginine was ultrasonically dispersed in ultrapure water to obtain a 2% L-arginine dispersion. The weighed heterogeneous cascade nanozyme material was ultrasonically dispersed in ultrapure water to obtain a heterogeneous cascade nanozyme material dispersion with a concentration of 250 μg / mL. The above L-arginine dispersion and heterogeneous cascade nanozyme material dispersion were added to the above hydrogel base liquid, and ultrasonically mixed to obtain a hydrogel precursor solution.

[0129] The weighed calcium chloride was ultrasonically dispersed in ultrapure water to obtain a calcium chloride aqueous solution with a mass concentration of 0.12 mol / L. The calcium chloride aqueous solution was added to the hydrogel precursor solution and mixed evenly, cross-linked for 5 minutes to form a crude hydrogel, and the obtained crude hydrogel was placed in liquid nitrogen for 4 hours, followed by freeze drying for 24 hours to obtain the injectable heterogeneous cascade nanozyme antibacterial hydrogel.

[0130] Comparative Example 1

[0131] The difference between this comparative example and Example 1 is only that:

[0132] This comparative example does not load L-arginine and heterogeneous cascade nanozyme materials, that is, the hydrogel material provided in this comparative example is sodium alginate hyaluronic acid hydrogel, denoted as S / H.

[0133] Comparative Example 2

[0134] The difference between this comparative example and Example 1 is only that:

[0135] In this comparative example, glucose oxidase, L-arginine and hydrogel material are not compounded, that is, the material provided in this comparative example is nanocomposite particles, which are recorded as MoS2@CeO2.

[0136] Comparative Example 3

[0137] The difference between this comparative example and Example 1 is only that:

[0138] In this comparative example, cerium dioxide, glucose oxidase, L-arginine and hydrogel material are not compounded, that is, the material provided in this comparative example is a single nanoflower-shaped molybdenum disulfide nanoparticle, denoted as MoS2.

[0139] Comparative Example 4

[0140] The difference between this comparative example and Example 1 is only that:

[0141] In this comparative example, no hydrogel material is compounded, that is, the material provided in this comparative example is a heterogeneous cascade nanozyme material, denoted as MoS2@CeO2-GOx.

[0142] Comparative Example 5

[0143] The difference between this comparative example and Example 1 is only that:

[0144] In this comparative example, the nanoflower-shaped molybdenum disulfide nanoparticles, glucose oxidase, L-arginine and hydrogel material are not composited, that is, the material provided in this comparative example is a single cerium dioxide nanozyme, denoted as CeO2.

[0145] Experimental Section

[0146] Through analysis, the present invention finds that Examples 1 to 3 have similar structural features. Those skilled in the art should know that structure determines properties, and similar structures indicate that Examples 1 to 3 have similar performance characteristics. Therefore, in order to avoid redundancy, the present invention will take Example 1 as an example to analyze and explain its structure and performance.

[0147] (I) Morphology test

[0148] 1) Macromorphology test

[0149] The present invention photographs and records the macroscopic morphologies of the injectable heterogeneous cascade nanozyme antibacterial hydrogel of Example 1 and the sodium alginate hyaluronic acid hydrogel of Comparative Example 1, and the recording results are as follows: Figure 1 and Figure 2 As shown. Among them, Figure 1 This is a photo of the injectable heterogeneous cascade nanozyme antibacterial hydrogel of Example 1. Figure 2 This is a photograph of the sodium alginate hyaluronic acid hydrogel of Comparative Example 1.

[0150] Depend on Figure 1 and Figure 2 It can be seen from the test results that the hydrogel materials obtained in Example 1 and Example 2 have similar macroscopic morphologies.

[0151] 2) Micromorphology test

[0152] The present invention respectively carried out scanning electron microscope tests on the injectable heterogeneous cascade nanozyme antibacterial hydrogel of Example 1 and the sodium alginate hyaluronic acid hydrogel of Comparative Example 1, and the test results are as follows: Figure 3 and Figure 4 As shown. Among them, Figure 3 is a scanning electron microscope image of the injectable heterogeneous cascade nanozyme antibacterial hydrogel of Example 1, Figure 4 This is a scanning electron microscope image of the sodium alginate hyaluronic acid hydrogel of Comparative Example 1.

[0153] Depend on Figure 3 and Figure 4 It can be seen from the test results that the hydrogel materials obtained in Example 1 and Example 2 have similar microscopic morphologies, which indicates that after loading the heterogeneous cascade nanozyme material by the method of the present invention, it does not affect the original 3D network structure of the hydrogel and still maintains a good porous structure.

[0154] The present invention also carried out scanning electron microscope tests on MoS2 of Comparative Example 3 and MoS2@CeO2-GOx of Comparative Example 4, and the test results are as follows: Figure 5 shown.

[0155] Figure 5 The scanning electron microscope images of MoS2 of Comparative Example 3 and MoS2@CeO2-GOx of Comparative Example 4 are shown in Figure A. Figure A is the scanning electron microscope image of MoS2 of Comparative Example 3, and Figure B is the scanning electron microscope image of MoS2 of Comparative Example 4. By comparison Figure 5 It can be seen from Figures A and B that compared with single molybdenum disulfide nanoflowers, CeO2 NPs and GOx can be clearly observed attached to the MoS2 nanoflowers, and the thickness of the MoS2 nanopetals after loading CeO2 NPs and GOx becomes thicker and the morphology becomes rougher, but the nanoflower-like structure is still retained.

[0156] (ii) Transmission electron microscope test

[0157] The present invention also conducted a transmission electron microscope test on the MoS2@CeO2-GOx of Comparative Example 4, and the test results are as follows: Figure 6 shown.

[0158] Depend on Figure 6 The test results clearly show that cerium dioxide nanoparticles and glucose oxidase are confined in the nano-petals. The nano-petals appear thick and the surface load is significantly increased. After loading CeO2 NPs and GOx on the MoS2 nano-flowers, they still maintain a good flower shape, which indicates that loading CeO2 NPs and GOx by the method of the present invention will not affect the original MoS2 nano-flower structure.

[0159] (III) Zeta potential analysis

[0160] The present invention tests and analyzes the Zeta potential of the materials provided in Comparative Examples 2 to 5, and the test and analysis results are as follows: Figure 7 As shown, it can be seen that the Zeta potential of MoS2 alone is a negative potential of approximately -40mv±0.1mv, while the Zeta potential of CeO2 is a positive potential of approximately +30mv±0.5mv. Since the two have opposite charges, MoS2@CeO2 with a Zeta potential of approximately +30mv±0.1mv is obtained through strong electrostatic interaction. The GOx loaded by the present invention is negatively charged, and the Zeta potential of MoS2@CeO2-GOx obtained after GOx loading is approximately +20mv±0.4mv, which also shows that CeO2 and GOx are successfully loaded on MoS2 through the present invention.

[0161] (IV) XPS analysis

[0162] The present invention respectively performs X-ray photoelectron spectroscopy analysis on the materials provided in Comparative Example 3 and Comparative Example 4, and the test analysis results are as follows: Figure 8 As shown, it can be seen that after the in-situ deposition of CeO2 and the loading of GOx, the 3d orbital of the Ce element, the 1s orbital of the C element, and the 1s orbital of the O element were enhanced, respectively, which once again shows that MoS2@CeO2-GOx was successfully prepared by the method of the present invention.

[0163] (V) Antibacterial performance test

[0164] Considering that the hydrogel matrix in the injectable heterogeneous cascade nanozyme antibacterial hydrogel of the present invention has no toxic side effects, in order to explore the effect of the injectable heterogeneous cascade nanozyme antibacterial hydrogel on normal cells, the present invention takes the loaded heterogeneous cascade nanozyme material as an example and conducts the following tests:

[0165] 1) Preparation of primary seed solution: 1 mL of fresh LB nutrient broth (Shanghai Shenggong Biotechnology) culture medium was added to the freeze-dried powder of Gram-positive bacteria - Staphylococcus aureus (S. aureus, ATCC6538), Bacillus subtilis (Bacillus subtilis, ATCC 6633) and Gram-negative bacteria - Escherichia coli (E. coli, ATCC25922) purchased from the American Type Culture Collection (ATCC) to dissolve the bacteria, and the entire bacterial solution was transferred to a conical flask containing 20 mL of fresh LB culture medium, and incubated in a constant temperature oscillator at 37°C at a shaking rate of 180 rpm overnight to activate the bacteria to obtain a primary seed solution.

[0166] 2) Preparation of secondary seed solution: 10 μL of each primary seed solution was transferred to 10 mL of fresh LB culture medium, placed in a constant temperature oscillator at 37°C and incubated at a shaking rate of 180 rpm for 8 h, and the absorbance of the bacterial solution at 600 nm (OD 600 ) Determine bacterial concentration, OD 600 The range is between 0.6-0.8, and the secondary seed solution in the logarithmic growth phase is obtained.

[0167] 3) Determination of growth curve:

[0168] ①Sample dilution:

[0169] Take 1 mg of the MoS2@CeO2-GOx nanomaterial of comparative example 4 and dissolve it in 1 mL of LB culture medium, and add 2 mg of L-arginine to obtain a mixture of heterogeneous cascade nanozyme material and L-arginine to obtain an experimental sample to simulate the hydrogel material of Example 1, recorded as MoS2@CeO2-GOx+L-Arg.

[0170] ②96-well plate detection growth inhibition curve:

[0171] Ⅰ) In a 96-well plate, 200 μL of fresh LB culture medium was added to the wells in the top row, leftmost column, and bottom row as blank controls.

[0172] II) Add 100 μL of fresh LB culture medium to the remaining wells except the second column.

[0173] III) Add 200 μL of the above experimental samples to the remaining wells in the second column.

[0174] IV) Pipette 100 μL of sample solution from the second column of wells containing sample solution and transfer to the next column of wells containing 100 μL of fresh LB culture medium, mix well, and dilute to the tenth concentration in sequence. At the same time, discard the excess 100 μL of sample dilution solution in the column of wells diluted to the tenth concentration.

[0175] V) Dilute the secondary seed bacterial solution by an appropriate multiple and transfer 100 μL to each well of a 96-well plate containing 100 μL of solution.

[0176] VI) After adding the bacterial solution, the 96-well plate was placed in a biochemical incubator at a constant temperature and humidity of 37°C for incubation.

[0177] The present invention measures the OD of the solution in the 96-well plate every 2 hours. 600 And record it, and organize it and draw it as follows Fig. 9 The inhibitory growth curves of different concentrations of MoS2@CeO2-GOx+L-Arg on Staphylococcus aureus and Escherichia coli are shown.

[0178] The present invention also analyzes the growth of bacteria added to samples of different concentrations at different time periods and calculates the antibacterial rate according to the following formula:

[0179] Antibacterial rate (%) = (OD 对照例 -OD 实验样品 ) / (OD 对照例 )×100%.

[0180] Fig. 9 Figure 1 is the inhibitory growth curve of different concentrations of MoS2@CeO2-GOx+L-Arg on Staphylococcus aureus and Escherichia coli. Figure A is the inhibitory growth curve of different concentrations of MoS2@CeO2-GOx+L-Arg on Staphylococcus aureus, and Figure B is the inhibitory growth curve of different concentrations of MoS2@CeO2-GOx+L-Arg on Escherichia coli.

[0181] Depend on Fig. 9 From the test results of Figures A and B, it can be seen that MoS2@CeO2-GOx+L-Arg shows a gradually enhanced antibacterial effect with the increase of concentration, and the minimum inhibitory concentration (MIC) for Staphylococcus aureus is 2μg / mL, and the minimum inhibitory concentration (MIC) for Escherichia coli is 16μg / mL.

[0182] The present invention summarizes the antibacterial activity experimental results of the MoS2@CeO2-GOx+L-Arg prepared above and the control example as shown in Table 1.

[0183] Table 1 Antibacterial activity test results

[0184]

[0185] It can be seen from the test results in Table 1 that compared with the control group, MoS2@CeO2-GOx+L-Arg showed significant synergistic antibacterial effects on both Gram-positive bacteria Staphylococcus aureus and Gram-negative bacteria Escherichia coli, and the killing effect was dose-dependent, which indicates that the cascade nanozyme composite material prepared by the method of the present invention has excellent in vitro antibacterial properties.

[0186] The present invention further analyzes the bactericidal kinetic experimental data of MoS2@CeO2-GOx+L-Arg on Staphylococcus aureus and Escherichia coli, and organizes them as follows: Fig.10 The bactericidal kinetics statistical diagram is shown.

[0187] Fig.10 Figure 1 is the time-killing curve of MoS2@CeO2-GOx+L-Arg against Staphylococcus aureus and Escherichia coli, that is, the bactericidal kinetic statistical diagram of MoS2@CeO2-GOx+L-Arg against Staphylococcus aureus and Escherichia coli, respectively. Figure A is the bactericidal kinetic statistical diagram of MoS2@CeO2-GOx+L-Arg against Staphylococcus aureus, and Figure B is the bactericidal kinetic statistical diagram of MoS2@CeO2-GOx+L-Arg against Escherichia coli. In the figure, MIC means minimum inhibitory concentration, that is, 8MIC means that the concentration is 8 times the minimum inhibitory concentration MIC value.

[0188] Depend on Fig.10 From the test results, it can be seen that for Staphylococcus aureus, when the concentration reaches 2 times the MIC value, bacterial death occurs in 6 hours, while for Escherichia coli, when the concentration is 4 MIC, bacterial death occurs in 4 hours.

[0189] The above antibacterial experiments can effectively prove that the heterogeneous cascade nanozyme composite material obtained in Example 1 has high antibacterial activity and is the selected antibacterial material.

[0190] (VI) Biocompatibility analysis

[0191] In order to verify the biocompatibility of the cascade nanozyme composite material of the present invention, the present invention still takes the MoS2@CeO2-GOx+L-Arg sample prepared above as an example and conducts the following tests on it:

[0192] Sheep red blood cells were used to detect the cell hemolytic ability of MoS2@CeO2-GOx+L-Arg samples. 1.5mL of 4% sheep red blood cells were taken into a 2mL centrifuge tube, centrifuged at 3000rpm for 5min, and the red blood cell preservation solution was gently removed. Then 1.5mL of normal saline was added and gently blown evenly. After centrifugation at 3000rpm for 5min, the supernatant was removed and the sample was resuspended in 1.5mL of normal saline. 1% Triton was used as a positive control, i.e., the Positive group; normal saline was used as a negative control, i.e., the Saline group. The 4% red blood cell suspension was incubated with different concentrations of MoS2@CeO2-GOx+L-Arg samples of 0 μg / mL, 1 μg / mL, 2 μg / mL, 4 μg / mL, 8 μg / mL, 16 μg / mL, 32 μg / mL, 64 μg / mL, 128 μg / mL and 256 μg / mL in a constant temperature oscillator at 37 °C for 1 h, and then centrifuged at 3000 rpm for 5 min, and the suspension was collected to detect the absorbance at 540 nm, i.e., OD 540 Finally, the hemolysis rate was calculated according to the following formula:

[0193] Red blood cell hemolysis rate (%) = (OD 样品 -OD 生理盐水 ) / (OD 1%曲拉通 -OD 生理盐水 )×100%.

[0194] Fig.11 The in vitro hemolysis rate statistics of MoS2@CeO2-GOx+L-Arg at different concentrations are shown in Figure 2. Fig.11 The illustrations in the figure are the actual pictures of the samples after 1 hour of shaking incubation. Fig.11 From the test results, it can be seen that MoS2@CeO2-GOx+L-Arg has a lower red blood cell hemolysis rate. Even if the concentration of MoS2@CeO2-GOx+L-Arg reaches 256μg / mL, the hemolysis rate of 4% red blood cells is still lower than 5%, which meets the safety range of in vivo experiments of nanomaterials. This shows that the heterogeneous cascade nanozyme composite material prepared by the present invention has good biocompatibility.

[0195] (VII) Analysis of in vivo therapeutic effects

[0196] In order to verify that the cascade nanozyme composite material of the present invention has a good in vivo therapeutic effect, the present invention still takes the MoS2@CeO2-GOx+L-Arg sample prepared above as an example and performs a diabetic wound infection test on it:

[0197] Establishing diabetic wound infection in mice to evaluate antimicrobial efficacy:

[0198] (1) First, create a 7mm to 10mm wound on the back of the diabetic mouse near the right leg, and then dilute the logarithmic phase Staphylococcus aureus solution to OD 600 After the pH value is between 0.88 and 1.1, 150 μL to 200 μL of bacterial solution is injected into the wound to infect the wound.

[0199] (2) All diabetic mice with wound infection were observed, and 50 infected mice with successful modeling were selected and divided into five groups according to the size of the wound area, namely Group I, Group II, Group III, Group IV, and Group V, with five infected mice in each group.

[0200] (3) The mice were divided into groups and injected with drugs at the wound site: Group I was injected with 300 μL of saline solution every two days; Group II was injected with 300 μL of 250 μg / mL MoS2@CeO2-GOx+L-Arg saline solution every two days; Group III was injected with 300 μL of 300 μg / mL MoS2@CeO2-GOx+L-Arg saline solution every two days; Group IV was injected with 300 μL of 350 μg / mL MoS2@CeO2-GOx+L-Arg saline solution every two days; Group V was injected with 300 μL of 400 μg / mL MoS2@CeO2-GOx+L-Arg saline solution every two days.

[0201] (4) The drug was administered continuously for 10 days, and photos were taken every two days to record the changes in the infected wounds of each group of mice.

[0202] The present invention organizes the changes in the infected wounds of each group of mice as follows: Fig.12 As shown, according to Fig.12 The changes in the infected wound area of ​​each group of mice were quantified and sorted as follows: Fig.13 As shown. Among them, Fig.12 This is a diagram of the wound changes in diabetic mice against Staphylococcus aureus infection after injection of different concentrations of MoS2@CeO2-GOx+L-Arg. Fig.13 Quantification of wound area against Staphylococcus aureus infection in diabetic mice after injection of different concentrations of MoS2@CeO2-GOx+L-Arg.

[0203] Depend on Fig.12 and Fig.13 The test results show that compared with the drug-treated groups II to V, the infected wounds of mice in the blank control group of group I recovered poorly after 10 days of treatment; while obvious wound healing was observed in the mice in the drug-treated group treated with MoS2@CeO2-GOx+L-Arg, indicating that the prepared cascade nanozyme composite material has excellent in vivo antibacterial activity and the ability to promote wound repair.

Claims

1. A method for preparing an injectable heterogeneous cascade nanozyme antibacterial hydrogel, characterized in that: The following steps are involved: The cerium salt is ultrasonically dispersed in oleylamine, and then xylene is added and mixed, and after heating to 85°C to 95°C, water is added to obtain a cerium dioxide nanozyme seed solution; MoS2 nanoparticles with a nanoflower structure are used as spatial confinement carriers, and added to the cerium dioxide nanozyme seed solution to obtain a mixed solution; The mixed solution is heated at 85°C to 95°C to react, so as to in situ deposit the cerium dioxide nanozyme on the surface of the MoS2 nanoparticles through a reverse micelle reaction to obtain nanocomposite particles; In a solution environment, the nanocomposite particles are used as carriers and glucose oxidase is used as a load, and glucose oxidase is loaded on the surface of the nanocomposite particles through electrostatic interaction to obtain a heterogeneous cascade nanozyme material; In water, sodium alginate and hyaluronic acid are evenly dispersed to obtain a hydrogel base liquid; NO donor and heterogeneous cascade nanozyme material are sequentially dispersed in the hydrogel base liquid to obtain a hydrogel precursor liquid; a cross-linking agent is added to the hydrogel precursor liquid so that the hydrogel base liquid is fully cross-linked under the action of the cross-linking agent to form a hydrogel with a three-dimensional network structure, and at the same time, the NO donor and the heterogeneous cascade nanozyme material are evenly dispersed in the three-dimensional network structure of the hydrogel to obtain the injectable heterogeneous cascade nanozyme antibacterial hydrogel.

2. The method for preparing the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 1, characterized in that: The cerium salt is cerium chloride heptahydrate; The usage ratio of the oleylamine to the cerium salt is 3 mL to 4 mL: 0.1 mmol; The dosage ratio of the xylene to the cerium salt is 10 mL to 20 mL: 0.1 mmol; The dosage ratio of the molybdenum disulfide nanoparticles to the cerium salt is 0.5 to 1:

1.

3. The method for preparing the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 1, characterized in that: The NO donor is L-arginine; In the hydrogel precursor solution, the amount of the NO donor added is 1 to 1.5 times the amount of the sodium alginate added.

4. The method for preparing the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 1, characterized in that: In the hydrogel precursor solution, the added amount of the heterogeneous cascade nanozyme material is 0.1 to 0.2 times the added amount of the sodium alginate.

5. The method for preparing the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 1, characterized in that: The heterogeneous cascade nanozyme material is prepared by the following steps: dispersing the nanocomposite particles in water to obtain a nanocomposite particle dispersion; dispersing glucose oxidase in water to obtain a glucose oxidase aqueous solution; The glucose oxidase aqueous solution is added dropwise to the nanocomposite particle dispersion, and the mixture is stirred at room temperature to load the glucose oxidase on the surface of the nanocomposite particles through electrostatic interaction, and the solid-liquid separation is performed. After the precipitate is freeze-dried, a heterogeneous cascade nanoenzyme material is obtained; Wherein, the stirring reaction time is 8h to 16h.

6. The method for preparing the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 1, characterized in that: The mass ratio of the glucose oxidase to the nanocomposite particles is 1.8-2.2:

1.

7. The method for preparing the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 1, characterized in that: The mass ratio of the sodium alginate to the hyaluronic acid is 1.8-2.2:

1.

8. The method for preparing the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 1, characterized in that: The cross-linking agent is calcium chloride; The mass ratio of the cross-linking agent to the sodium alginate is 0.8-1.2:

2.

9. An injectable heterogeneous cascade nanozyme antibacterial hydrogel as claimed in any one of claims 1 to 8.

10. An application of the injectable heterogeneous cascade nanozyme antibacterial hydrogel according to claim 9 in the antibacterial field, characterized in that: The injectable heterogeneous cascade nanozyme antibacterial hydrogel is used to fight pathogenic bacteria; The anti-pathogenic bacteria are one or more of Staphylococcus aureus, Escherichia coli, Bacillus subtilis, methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa.

Citation Information

Patent Citations

  • Injectable antibacterial hydrogel for promoting healing of diabetes infected wound as well as preparation method and application of injectable antibacterial hydrogel

    CN117085170A

Cited By

  • Low-irritation cerium oxide nano-enzyme solution and preparation method thereof

    CN120837524A

  • Cerium nano-enzyme composite active material and application thereof in hepatic failure treatment

    CN120866210A

  • A cerium nanoscale enzyme composite active material and its application in liver failure treatment

    CN120866210B